The non-designer's presentation book : principles for effective presentation design - Williams, Robin, 1953- (Peachpit Press, 2010)
These days, it's not just corporate marketing directors tasked with giving computer-based presentations--anyone forced to stand in front of a crowd and talk for more than three minutes had better know how to put together a slide presentation. You're not a professional designer, but you want your slides to look professional. What do you do? Enter Robin Williams , the beloved, best-selling non-designer's designer (with over 850,000 copies of The Non-Designer's Design Book in print!) who has taught an entire generation the basics of design and typography. In The Non-Designer's Presentation Book, Robin expands upon the design principles introduced in her award-winning Non-Designer's series. She explains four fundamental principles of good design as applied to digital presentations, and adds four more principles specific to clear communication with slides. Whether you work with a Mac or PC, PowerPoint or Keynote, let Robin guide you, in her signature, light-hearted style, through the entire process of creating a presentation--from using the right software to organizing your ideas to designing effective, beautiful slides that won't put your audience to sleep. In this essential guide to presentation design, you'll learn: What makes a good presentation or a bad one How to plan, organize, and outline your presentation Four principles of designing effective presentations Four principles for designing beautiful slides that communicate clearly An exhaustive list of timeless presentation rules...that you should totally ignore.